2022
DOI: 10.3390/cancers14071736
|View full text |Cite
|
Sign up to set email alerts
|

Interspatial Distribution of Tumor and Immune Cells in Correlation with PD-L1 in Molecular Subtypes of Gastric Cancers

Abstract: (1) Background: EBV-positive and mismatch repair-deficient (MMRd) gastric cancers (GCs) show higher levels of tumor-infiltrating lymphocytes (TILs) and PD-L1 expression and thus a more profound response to immunotherapy. However, the majority of GCs are EBV-negative (EBV−) and MMR proficient (MMRp). We analyzed PD-L1 expression and TILs in EBV-MMRpGCs in comparison to EBV-positive (EBV+) and MMRdGCs to identify an immunogenic phenotype susceptible to immunotherapy. (2) Methods: A next-generation tissue microar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(57 reference statements)
1
1
1
Order By: Relevance
“…The expression of these anti-tumor immunity molecules is also characteristic of a T cell-inflamed phenotype [ 65 ]. Our bioinformatic observations are supported by many other reports that EBVaGCs express higher levels of PDL1 protein [ 66 , 67 , 68 , 69 , 70 , 71 ]. In vitro work has also definitively shown that many EBVaGC cell lines expressed high levels of PDL1, which functionally contributed to the suppression of T cell proliferation [ 71 ].…”
Section: Discussionsupporting
confidence: 89%
“…The expression of these anti-tumor immunity molecules is also characteristic of a T cell-inflamed phenotype [ 65 ]. Our bioinformatic observations are supported by many other reports that EBVaGCs express higher levels of PDL1 protein [ 66 , 67 , 68 , 69 , 70 , 71 ]. In vitro work has also definitively shown that many EBVaGC cell lines expressed high levels of PDL1, which functionally contributed to the suppression of T cell proliferation [ 71 ].…”
Section: Discussionsupporting
confidence: 89%
“…In nearly all cases, CD8+ TILs were present both in the tumor and the stromal compartment and correlated with PD-L1 positivity, which is in agreement with many previous studies. In contrast with previous studies on MSI-positive tumors, we found MSI positivity to be mutually exclusive with CD8+ TILs and nearly also with PD-L1 expression [ 38 , 39 , 40 ]. This may be due to the fact that we only applied PMS2, MLH1, MSH2, and MSH6 immunohistochemistry without the possibility to confirm our results by multiplex PCR.…”
Section: Discussioncontrasting
confidence: 99%
“…Some existing studies propose using EBV as an adjuvant predictor of immune response in GC patients [84]. For example, combining PD-L1 and CD8 could identify EBVaGCs with high immunoreactivity in patients with pMMR [85]. A real-world study by Yu et al found that better ORR and PFS were observed only in EBVaGC patients when they were combined with CPS ≥ 1 [86].…”
Section: Epstein-barr Virus Status As the Biomarker For Gc Immunotherapymentioning
confidence: 99%